Initiatives to promote agricultural research and experimentation in the Ministry of Agriculture of the Argentine Republic (1936-1948) (Quinto Sol, 2025)
This article analyzes a set of projects, debates, and achievements focused on the promotion of official agricultural research and experimentation in Argentina between 1936 and 1948. It presents the initiatives and discussions among technicians and political officials at the Argentine Ministry of Agriculture, which led to the generation of widely shared understandings regarding the importance of these activities and the best ways to organize them, including, for example, the need to create a central agency and multiple experimental stations. It also analyzes how this activity led to the passage, in 1948, of Law No. 13254, focused on the promotion of agricultural research and experimentation. In line with these developments, it suggests the existence of an institutional accumulation that transcended the important political changes experienced by the country in those years, with consequences for the subsequent creation of the National Institute of Agricultural Technology.
Keywords: history of science; State; agricultural research